Sport-related femoral artery occlusion detected by near-infrared spectroscopy and pedal power measurements: a case report. Issue 2 (3rd April 2021) - van Hooff, Martijn; Schep, Goof; Bender, Mart; Scheltinga, Marc; Savelberg, Hans
ABSTRACT: Objectives: Approximately one in five professional cycling athletes will eventually develop a sport-related vascular problem. However, detecting such flow limitation is a diagnostic challenge as the sensitivity of the currently available standard diagnostic tools is limited. Methods: Here we present an athlete with exercise-induced pain and weakness of the left leg. During the physical examination, pulsations of the femoral artery were palpable but less prominent. He was analyzed in an ongoing research project aimed at improving methods detecting sport-related leg flow limitations. Results: During functional testing, the ankle-brachial index of the left leg was moderately lowered. However, results of near-infrared spectroscopy and pedal power measurements were largely abnormal suggesting a severe flow limitation. Conclusion: Combining post-exercise ankle-brachial index, near-infrared spectroscopy, and pedal power measurements as routine diagnostic functional testing suggested a severe arterial flow inflow limitation. Conventional diagnostics encompassing duplex-Doppler echography and magnetic resonance angiography confirmed a femoral artery occlusion. Clinical trial registration: https://www.trialregister.nl/ identifier is Trial NL8557.Abbreviations : NIRS: Near-Infrared Spectroscopy; PPM: Pedal Power Measurements; ABI: Ankle Brachial Index; PSV: Peak Systolic Velocity